Respuesta :

Answer:5

Step-by-step explanation:

Simplifying

8x + -20 = 3x + 5

Reorder the terms:

-20 + 8x = 3x + 5

Reorder the terms:

-20 + 8x = 5 + 3x

Solving

-20 + 8x = 5 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.

-20 + 8x + -3x = 5 + 3x + -3x

Combine like terms: 8x + -3x = 5x

-20 + 5x = 5 + 3x + -3x

Combine like terms: 3x + -3x = 0

-20 + 5x = 5 + 0

-20 + 5x = 5

Add '20' to each side of the equation.

-20 + 20 + 5x = 5 + 20

Combine like terms: -20 + 20 = 0

0 + 5x = 5 + 20

5x = 5 + 20

Combine like terms: 5 + 20 = 25

5x = 25

Divide each side by '5'.

x = 5

Simplifying

x = 5